In Situ Chemical Oxidation of Ultrasmall MoOx Nanoparticles in Suspensions - Yun-Ju Lee; Diego Barrera; Kaiyuan Luo; Julia W. P. Hsu (Journal of Nanotechnology)
Nanoparticle suspensions represent a promising route toward low cost, large area solution deposition of functional thin films for applications in energy conversion, flexible electronics, and sensors. However, parameters such size, stoichiometry, and electronic properties must be controlled to achieve best results for the target application. In this report, we demonstrate that such control can be achieved via in situ chemical oxidation of MoOx nanoparticles in suspensions. Starting from a microwave-synthesized suspension of ultrasmall (d~2 nm) MoOx nanoparticles in n-butanol, we added H2O2 at room temperature to chemically oxidize the nanoparticles. We systematically varied H2O2 concentration and reaction time and found that they significantly affected oxidation state and work function of MoOx nanoparticle films. In particular, we achieved a continuous tuning of MoOx work function from 4.4 to 5.0 eV, corresponding to oxidation of as-synthesized MoOx nanoparticle (20% Mo6+) to essentially pure MoO3. This was achieved without significantly modifying nanoparticle size or stability. Such precise control of MoOx stoichiometry and work function is critical for the optimization of MoOx nanoparticles for applications in organic optoelectronics. Moreover, the simplicity of the chemical oxidation procedure should be applicable for the development of other transition oxide nanomaterials with tunable composition and properties.